2022
DOI: 10.1080/10705422.2022.2073308
|View full text |Cite
|
Sign up to set email alerts
|

Youth participation in policy-making processes in the United Kingdom: a scoping review of the literature

Abstract: Young people's voices remain underrepresented in health policy processes. This scoping review focuses on the United Kingdom (UK) and investigates how and to what degree young people have participated in policy-making processes. We adapt an established framework categorising how young people are involved in policy-related processes, ranging from advisory roles to communicating findings. We report a spectrum of practical examples, highlighting opportunities for successful policymaking with youth, in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The unique perspectives of day-to-day life in foster care are unlikely to be captured through quantitative methods. There continues to be ongoing support for youth involvement in service design, delivery and policy initiatives 17–20. Yet, few studies include them 21–23.…”
Section: Introductionmentioning
confidence: 99%
“…The unique perspectives of day-to-day life in foster care are unlikely to be captured through quantitative methods. There continues to be ongoing support for youth involvement in service design, delivery and policy initiatives 17–20. Yet, few studies include them 21–23.…”
Section: Introductionmentioning
confidence: 99%
“…Recent projects have invited young people to contribute to the design of interventions for the promotion of healthy diets and physical activity [3][4][5][6] and obtain insights into their perspectives regarding body weight, 7 but such forms of youth engagement in obesity prevention research remain rare. 8 According to the UNICEF international charter for ethical research involving children, 9 research aiming to engage young people requires critical reflection to ensure that the rights, dignity, and wellbeing of youth are safeguarded. Researchers should recognize the young people's competencies, offer them opportunities for decision making and be aware of their varying capacities and social environments.…”
Section: Introductionmentioning
confidence: 99%
“…Developing obesity prevention strategies that specifically target young people and are adapted to their life circumstances and needs is therefore essential. Recent projects have invited young people to contribute to the design of interventions for the promotion of healthy diets and physical activity 3–6 and obtain insights into their perspectives regarding body weight, 7 but such forms of youth engagement in obesity prevention research remain rare 8 …”
Section: Introductionmentioning
confidence: 99%
“…In this context, a scoping review of publications describing the current state of child and youth participation in mental health policymaking is needed to guide and sustain future research and decision-making in this field. In our review, policymaking is broadly defined in a spectrum where participation can be found at different stages of a policy cycle, including research participation and dissemination of knowledge aiming to inform policies (Macauley et al, 2022;OECD, 2017).…”
Section: Introductionmentioning
confidence: 99%